The synthesis and highly effective antibacterial properties of Cu-3, 5-dimethy l-1, 2, 4-triazole metal organic frameworks - Xu, Xiaolin; Ding, Mengna; Liu, Kaiquan; Lv, Fujian; Miao, Yingchun; Liu, Yanmi; Gong, Ying; Huo, Yuning; Li, Hexing (Frontiers in Chemistry, 2023)
It has been investigated the influence of metal ions, the state of metal salt, and ligand on the sterilization ability of MOFs, and aims to achieve effective sterilization. Initially, the MOFs was synthesized by elements of Zn, Ag and Cd for the same period and para-family around Cu. It illustrated the atomic structure of Cu was more beneficial for coordinating with ligands. To further induce the maximum amount of Cu2+ ions in the Cu-MOFs to achieve the highest sterilization, various Cu-MOFs synthesized by different valence of Cu, various state of copper salts and organic ligands were performed, respectively. The results demonstrated that Cu-MOFs only synthesized by 3, 5-dimethyl-1, 2, 4-triazole and tetrakis (acetonitrile) copper(I) tetrafluoroborate presented the largest inhibition-zone diameter of 40.17 mm towards Staphylococcus Aureus (S. aureus) under dark condition. The proposed mechanism was Cu (Ⅱ) in MOFs could significantly cause multiple toxic effects, such as generation of reactive oxygen species, and lipid peroxidation in S. aureus cells, when the bacteria was anchored by the Cu-MOFs via electrostatic interaction. Finally, the broad antimicrobial properties for E. coli (E. coli), A. baumannii (A. baumannii) and S. aureus on Cu-MOFs were demonstrated. In conclusion, the Cu-3, 5-dimethyl-1, 2, 4-triazole MOFs appeared to be a potential antibacterial catalyst in the antimicrobial field.